PENGARUH ULASAN ONLINE, RATING, BEAUTY VLOGGER REVIEW DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK LIPSTIK HANASUI DI INDONESIA - Fitria Nursatika; Yuniorita Indah Handayani; Tamriatin Hidayah (Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of online reviews, rating, beauty vlogger reviews and prices on purchasing decisions for Hanasui Lipstick products in Indonesia. The population used in this study is consumers who have purchased Hanasui lipstick products online at marketplaces in Indonesia. The sample used was 140 respondents who met the criteria. The criteria in question are having purchased a Hanasui Lipstick product at least once online in the marketplace, a Hanasui Lipstick product user, at least 17 years – 40 years old and accessing Youtube and Tiktok as media to view product reviews from beauty vloggers. Sampling was carried out using a purposive sampling method, namely Non-probability Sampling. The method of data analysis with the help of SPSS 26. The tests used are instrument tests (validity test and reliability test), classical assumption test (normality test, multicollinearity test and heteroscedasticity test), multiple liniear regression analysis test, coefficient of determination test and hypothesis testing (t test and F test). The results of this study indicate that online reviews partially have no effect on purchasing decisions. Ratings, Beauty Vlogger Reviews and Prices partially influence Purchase decisions. Simultaneously Online Reviews, Ratings, Beauty Vlogger Reviews and Prices influence Purchasing Decisions.